Respuesta :

[tex]6x^2 +17x -3\\\\=6x^2 +18x-x-3\\ \\=6x(x+3)-(x+3)\\ \\=(x+3)(6x-1)\\\\\text{The length and width of the rectangle are}~ (6x-1)~ \text{and}~ (x+3)[/tex]

Answer:

[tex]\textsf{length}=6x - 1[/tex]

[tex]\textsf{width}=x+3[/tex]

Step-by-step explanation:

Area of a rectangle = length × width

Given area:  [tex]A=6x^2+17x-3[/tex]

Therefore,  [tex]6x^2+17x-3=\sf length \cdot width[/tex]

To find the length and width, we need to factorize the given expression for area.

To factor a quadratic in the form [tex]ax^2+bx+c[/tex]

  • Find 2 two numbers (d and e) that multiply to ac and sum to b
  • Rewrite b as the sum of these 2 numbers: d + e = b
  • Factorize the first two terms and the last two terms separately, then factor out the comment term.

[tex]6x^2+17x-3 \implies a=6, b=17, c=-3[/tex]

[tex]ac=6 \cdot -3=-18[/tex]

[tex]d+e=17[/tex]

So we are looking for a pair of numbers that multiply to -18 and sum to 17.

Factors of 18: 1, 2, 3, 6, 9, 18

Therefore, the two numbers (d and e) that multiply to -18 and sum to 17 are:

18 and -1

Rewrite [tex]17x[/tex] as [tex]+18x-x[/tex]:

[tex]\implies 6x^2+18x-x-3[/tex]

Factor first two terms and last two terms separately:

[tex]\implies 6x(x+3)-1(x+3)[/tex]

Factor out common term [tex](x+3)[/tex]:

[tex]\implies (6x-1)(x+3)[/tex]

As length > width,

[tex]\textsf{length}=6x - 1[/tex]

[tex]\textsf{width}=x+3[/tex]